Influence Brand Equity, Lifestyle, And Product Variation On The Decision To Purchase Geoff Max Shoes In Ngadisimo Kediri City - Priyandani, Andy; Raharjo, Itot Bian (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim :The purpose of this study was to determine the influence of brand equity, lifestyle, and product variation on purchasing decisions for Geoff Max shoes in Ngadisimo, Kediri City. Design/Method/Approach: The method used in this research is quantitative.Sampling technique using techniquenonprobability sampling. The sample taken in this study were consumers who bought and wore Geoff Max shoes totaling 40 people. This study used classical assumption analysis techniques, multiple linear regression and hypothesis testing (t-test and F-test). Research Findings :The results of the t-test study showed that the variables of brand equity, lifestyle, and product variation partially had a significant effect on purchasing decisions. Based on the results of the F test, it is known that the variables of brand equity, lifestyle, and product variation simultaneously have a significant effect on purchasing decisions. Theoretical contribution/Originality :This research brings together key concepts in marketing (brand equity, lifestyle, and product variety) and provides new insights into how these three factors interact to shape consumer purchasing decisions, particularly in the context of a local brand such as Geoff Max.  Practitionel/Policy implications :This research provides Geoff Max company with strategic guidance that can be applied immediately to strengthen the brand's position in the market. Strengthening brand equity, adjusting to consumer lifestyles, increasing product variety, will support purchasing decisions. By continuing to innovate and adjust products and marketing to the needs of Geoff Max can increase competitiveness and achieve company goals. Research limitations:Because in this study it is proven that there are still other variables such as price, product quality, consumer satisfaction, and others that influence purchasing decisions, this can be used as material for conducting similar further research in order to obtain better results.